(untitled) (Research, Society and Development, 2025)
Calotropis procera (Aiton) W.T. Aiton, known as silk flower, is a resilient forage species with high potential for biomass production in semi-arid regions. This study aimed to evaluate the productive and qualitative characteristics of Calotropis procera hay cultivated under different spacings and cutting heights. The experiment, conducted in a completely randomized design with four spacings, analyzed plant height, fresh and dry mass, and dry matter yield (DMY). The 1.0 × 1.0 m spacing showed the best performance (DMY of 39.1% and an average height of 112.4 cm). The hay exhibited good coloration, 12.6% crude protein, and high acceptance by sheep and goats, without adverse effects. It is concluded that C. procera represents a sustainable and low-cost alternative for animal feed in semi-arid regions, contributing to SDGs 2, 12, 13, and 15.